Beyond the doctorate: Exploring Indigenous Early Career Research trajectories - Locke, Michelle; Trudgett, Michelle; Page, Susan (The Australian Journal of Indigenous Education, 2022)
Growing research into the experiences of non-Indigenous early career researchers (ECRs) has identified a multitude of challenges that can impede early research career development. Expectations to publish, secure research grants and to deliver large teaching loads contribute to high levels of frustration and stress. While additional challenges - often associated with cultural work - have emerged in the literature with Australian and international Indigenous academics, research focused specifically on Indigenous Australian early career researchers is severely lacking. This paper begins with an examination of the Australian Indigenous pipeline to early career positions through undergraduate and postgraduate study. It reviews the trajectories of non-Indigenous early career researchers and then draws on emerging research with Indigenous academics in Australia and abroad to advocate specific investigation of the career trajectories of Indigenous Australian early career researchers. In accordance with a commitment from Australian universities to increase the number of Indigenous students and scholars, it is critical that experiences and needs of Indigenous early career researchers are investigated and understood. With a deeper level of understanding more effective strategies and systems can be implemented to better support and facilitate career trajectories of Indigenous Australian early career researchers and thus build a richer academy.